Presence of cerebral microbleeds is associated with cognitive decline in acromegaly - Xie, Zhengxing; Zhuang, Yan; Zhang, Zongqiang; Liu, Jieping (Frontiers in Oncology, 2022)
Background: The cognitive decline in acromegaly has gained increasing attention. Cerebral microbleeds (CMBs) as radiographic markers for microvascular injury have been linked to various types of cognitive decline. However, the association between CMBs formation and acromegaly has not yet been quantified. This study is designed to investigate the prevalence, radiographic patterns of CMBs and the association between cognitive function and acromegaly-related CMBs in growth hormone (GH) -secreting pituitary adenoma, which is characterized by acromegaly. Methods: In a cohort of 55 patients with GH-secreting pituitary adenoma (acromegaly) and 70 healthy control (HC) patients, we determined the presence of CMBs using a 3.0 Tesla MRI scanner. The numbers, locations and grades of CMBs were determined via susceptibility-weighted imaging (SWI) and the Microbleed Anatomical Rating Scale. Obstructive sleep apnea (OSA) was assessed using the criteria of the American Academy of Sleep Medicine (AASM) Scoring Manual Version 2.2. The Montreal Cognitive Assessment (MoCA) was used to assess cognitive performance within 3 days of admission. The association between CMBs and cognitive function as well as clinical characteristics was explored. Results: The incidence of CMBs was 29.1% whereas OSA 65.5% in acromegaly. There was a statistically significant difference in prevalence of CMBs between subjects with and without acromegaly (29.1%and5.3%, respectively) (p<0.01). The age of acromegaly patients with CMBs were much younger than that of HCs with CMBs. Compared with HCs, significant cognitive decline and occurrence of OSA were demonstrated in patients with acromegaly (p<0.01). Binary logistic regression analysis adjusted for age, education and body mass index (BMI) revealed that CMB was an independent risk factor for cognitive impairment in patients with acromegaly (OR=3.19, 95%CI 1.51-6.76, p =0.002). Furthermore, in the logistic regression models adjusted for age, BMI, diabetes and hypertension ,OSA was independently associated with the occurrence of CMBs in patients with acromegaly (OR=13.34, 95%CI 3.09-57.51, p =0.001). Conclusions: In conclusion, significantly increasing of CMBs was demonstrated in patients with acromegaly, which may be a result of OSA in acromegaly. The present study indicated increasing CMBs are responsible for cognitive decline in patients with acromegaly.